2016
DOI: 10.3126/jbmr.v1i2.15657
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Career Progression: A Study of the Perceptions of Nepali Women Employees

Abstract: Recent decades have witnessed unprecedented changes in workforce composition, resulting in women's increased involvement in the labor force. However, the proportion of women employees vary significantly within various organizational levels, with more women confined to junior level positions within organizations. This study, conducted in two phases, explored the career progression barriers as perceived by Nepali women employees to develop a set of 22-items questionnaire which was then used to examine how 114 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A cross-sectional mixed-methods investigation is conducted in 2016–2017. Academic literature reveals that mixed-method research schemes have proposed the sufficient strength of confirmatory results properly drawn from quantitative analysis, along with “deep structure” explanatory descriptions as drawn from qualitative analyses (Adhikary, 2016). The society of the investigation attends all women working for the financial department of listed firms in TSE (they are reasonably supposed to hold at least a four-year bachelor's degree in accounting).…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional mixed-methods investigation is conducted in 2016–2017. Academic literature reveals that mixed-method research schemes have proposed the sufficient strength of confirmatory results properly drawn from quantitative analysis, along with “deep structure” explanatory descriptions as drawn from qualitative analyses (Adhikary, 2016). The society of the investigation attends all women working for the financial department of listed firms in TSE (they are reasonably supposed to hold at least a four-year bachelor's degree in accounting).…”
Section: Methodsmentioning
confidence: 99%
“…Almost all working women are feeling physically tired due to the double work of inner and outer periphery of household, while the opposite situation is seen in the household with nonworking women. Women employees are hampered by individual, organizational, and societal structures that govern them (Adhikary, 2016). However, there is the good support of male members in the household chores in a family with working women.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents of the study notify their drive for progression in this career by listing some points as a commitment towards the job, positive synergies, dedication, dreaming about higher studies, and achievement motivation. Previous research has suggested that higher education with national and international degrees only can tighten the career of the academe (Adhikary, 2016). Female faculties have proven their enthusiasm and willingness to grab all the opportunities toward achieving higher degrees, possibly having family support (Khumaidah, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Saadin et al (2016) rightly identified that female's priority towards family life is seen as a barrier toward their progression. Similarly, Adhikary (2016) refers that although females are now capable of moving to a higher position they are halted by an invisible barrier. Barriers can be categorized into personal, societal, organizational, cultural, environmental, etc.…”
Section: Barriers Towards Teachingmentioning
confidence: 99%